PENGARUH PENAMBAHAN VITAMIN C (APM) PADA PAKAN TERHADAP KEMAMPUAN TUBUH MENGATASI STRES DAN PERTUMBUHAN IKAN PATIN (Pangasius Hypopthalmus) - Muhammad Thabri; Sukendi Sukendi; Syafriadiman Syafriadiman (Berkala Perikanan Terubuk, 2017)
The research was conducted from May to July 2016 in Aquaculture Technology Laboratory of Fisheries and Marine Science Faculty of Riau University. The method used was an experimental method, with Completely Randomized Design (CRD), and three levels of treatment. The treatments used the vitamin C APM (Ascorbyl Phosphate Magnesium) gives the doses diffrentiation, that were P1 (doses of vitamin C 0 mg/kg feed), P2 (doses of vitamin C 500 mg/kg feed) and P3 (doses of vitamin C 1.000 mg/kg feed). Result of this research showed that the vitamin C 1.000 mg/kg doses gived good resistance body of catfish (Pangasius hypopthalmus), from the stress effect, it si can showed from glucose of blood was fast down, at the beginning of blood glucose concentrations was 48,09 mg/dL, then the temperature shock give to fish after one hour 75,15 mg/dL and the last research showed was 49,73 mg/dL. And total of bood plasma were 5,13 g/dL, 3,30 g/dL and 4,72 g/dL respectively. The vitamin C 1000 mg/kg dose can also to increase the Specific Growth Rate (SGR), Food Conversion Ratio (FCR) and survival rate was 3,27 g; 82,92% and 100% respectively.